2022
DOI: 10.1029/2021pa004236
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoceanography of the Japan Sea Across the Mid‐Pleistocene Transition: Insights From IODP Exp. 346, Site U1427

Abstract: Introduction The Mid-Pleistocene Transition and the East Asian MonsoonThe Quaternary period is characterized by glacial-interglacial variability that has been linked to Earth's orbital cyclicity (e.g., Hays et al., 1976;Ruddiman, 2001). During the early part of the Quaternary, glacial-interglacial cycles varied at a frequency of 41,000 years (41 ka), but approximately half-way through the Quaternary, during the mid-Pleistocene, the glacial-interglacial cyclicity shifted to quasi 100,000 years (100 ka) cycles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 142 publications
(280 reference statements)
0
4
0
Order By: Relevance
“…Anoxic conditions are not strong and frequent between 1200 and 900 ka, and thereafter they occur periodically (Figure 6). Felder et al (2022) suggested that the Japan Sea had higher δ 18 O values during these periods of early middle Pleistocene transition (MPT) as the glacial conditions were severe. During this period sediment is characterized by high silt (>80%), high SS (%), high quartz and moderately sorted, (aeolian sediment characteristics) and the depositional environment is mainly affected by EAWM, westerly wind and minor riverine and IRD.…”
Section: During Middle Pleistocene Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anoxic conditions are not strong and frequent between 1200 and 900 ka, and thereafter they occur periodically (Figure 6). Felder et al (2022) suggested that the Japan Sea had higher δ 18 O values during these periods of early middle Pleistocene transition (MPT) as the glacial conditions were severe. During this period sediment is characterized by high silt (>80%), high SS (%), high quartz and moderately sorted, (aeolian sediment characteristics) and the depositional environment is mainly affected by EAWM, westerly wind and minor riverine and IRD.…”
Section: During Middle Pleistocene Transitionmentioning
confidence: 99%
“…Sediment records from marginal environments like the Japan Sea are challenging to analyse due to various factors, such as the palaeoceanographic reactions to climate change and the presence of terrestrial and marine signals (Tada et al, 1999). The Japan Sea responds to orbital to regional-scale climatic change and may be significantly more sensitive than the open oceans (Das et al, 2018(Das et al, , 2021Felder et al, 2022;Gallagher et al, 2018;Huang et al, 2018;Tada, 2004;Tada et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The waxing and waning of the ice will influence the oxygen isotopes, and the isotopic ratio changes indicating the foraminifera will record the sea level. Mg/Ca ratios will then discriminate the local freshwater effect from the global ice volume signal (Felder et al, 2022).…”
Section: Introductionmentioning
confidence: 99%